The Influence of Adversity Quotient, Need for Achievement, and Entrepreneurial Attitude on Entrepreneurial Intentionns - Maharani, Dina Fitriya; Indrawati, Aniek; Saraswati, Thusy Tiara (Jurnal Entrepreneur dan Entrepreneurship, 2020)
This study aims to determine the effect of adversity quotient and need for achievement on entrepreneurial intention through entrepreneurial attitude. This study uses a quantitative approach. The population in this study amounted to 155 people with a sample of 112 people. Sampling uses probability sampling with proportional random sampling. Data collection was carried out by using a questionnaire and documentation. To analyze the data, the researcher used descriptive statistical analysis, classic assumption test, path analysis and hypothesis testing using t test and multiple tests. The analysis shows that: (1) adversity quotient influences entrepreneurial attitude, (2) need for achievement influences entrepreneurial attitude, (3) adversity quotient influences entrepreneurial intention, (4) need for achievement influences entrepreneurial intention. (5) Entrepreneurial attitude influences entrepreneurial intention, (6) entrepreneurial attitude is able to mediate the effect of adversity quotient on entrepreneurial intention, (7) entrepreneurial attitude is able to mediate the influence of need for achievement on entrepreneurial intention.